Comparison of wastewater treatment in oil and gas industry using conventional methods (chemical, physical and biological). Issue 1 (November 2021) - Hamdy, M; Sudarno,; Huboyo, H S
Abstract: The oil and gas industry consumes tons of water, and the water produced from this industry contains harmful substances such as petroleum products and heavy metals that negatively affect humans and the environment. The objective of this research is to know the efficiency of the conventional wastewater treatment technologies (chemical by adding Alum, biological with aeration, and physical by filtration) to treat oily wastewater and the effect of the quantity of Alum on the treatment efficiency by using jar test and laboratory analysis beside modify the system to reuse the treated water in various activities. The treatment results showed a decrease of COD by 27%, BOD by 26.5%, oil and grease by 55%, and heavy metals by 95%, and the final results are compatible with the Egyptian standards. It is found that the optimum alum quantity that can be used is 15 mg/L which can remove 48% of oil and grease. Despite the simplicity and low cost of conventional methods for industrial wastewater treatment compared to advanced methods, they still give acceptable results. Reusing the treated water and sludge saves money, encouraging many industries to use it instead of discharging it.